Microstructural evolution, precipitation and mechanical properties of hot rolled 27Cr-4Mo-2Ni ferritic steel during 800 °C aging - Hui-Hu Lu; Hong-Kui Guo; Yi Luo; Zhen-Guang Liu; Wen-Qi Li; Jian-Chun Li; Wei Liang (Materials & Design, 2018)
A 27Cr-4Mo-2Ni super ferritic stainless steel was hot rolled and aged at 800 °C for times ranging from 10 min to 4 h to study the microstructure, precipitation and their effects on mechanical properties by using SEM, EBSD and TEM techniques. Experimental results demonstrate that a great deal of substructure, especially shear bands is obviously observed within elongated ferrite grains after hot rolling. After aging at 800 °C, Laves, chi and sigma phases are identified, and precipitation of these phases is accelerated evidently by the substructure. Laves phase particles are observed formed at dislocations and distributed inside grains with sub-micron scale. Precipitates of chi and sigma phase are found at grain boundaries and along shear bands, as well as around the TiN particles. Recovery during 800 °C aging is impeded by the precipitation of Laves phase at dislocations and chi phase at shear bands. Tensile ductility and micro hardness are significantly affected by the precipitation of intermetallics. The breakage pattern after tensile test transformed from ductile to brittle fracture when the aging time increases from 10 min to 4 h. Keywords: Ferritic steel, Aging treatment, Precipitation, Microstructure, Embrittlement